“We’re all travelers, all sojourners” : A pseudo-ethnography of incarceration and adaptation - Maria Virginia Aguilar; Edwin Falcis Lineses (Program Pascasarjana Universitas Negeri Yogyakarta, 2020)
The study intends to describe the dynamics in jail, the notable features of incarceration, and inmates' cultural premises to achieve adaptation to a different environment. Using participant observation and several indigenous methods of gathering data twenty inmates in a city jail were purposively selected for this qualitative study. Several findings are notable. First, traveling is a fitting metaphor to depict the inmate culture developed inside the jail, more so that it is consistent with how the inmates call their incarceration as a momentary biyahe, i.e., a sojourn. Second, the inmates reveal that a must-learn code of conduct patakaran or magna carta which is rooted in respect and discipline is essential to survival. Third, by tacit agreement with the jail management, the inmates have organized themselves with distinctive hierarchical roles that should be respected to maintain discipline and order. Each cell has its own structure to impose discipline and to accomplish every member's task. Fourth, a system of meting out punishment to the disobedience of rules is strictly enforced. Ultimately then, inmates adapt to a new environment and acquire behaviors appropriate to their community. Fifth, pockets of resistance are afforded, albeit in small and imperceptible manners. The study concludes that the facility's culture is dynamic, and inmates assert their roles beyond the prevailing social and structural forces.